Farmer-to-farmer video: Growing cassava on sloping land (Vietnamese version) - International Center for Tropical Agriculture; Agro-Insight (2015)
This farmer-to-farmer video, developed through funding by the Swiss Agency for Development and Cooperation (SDC) by CIAT and Agro-Insight, explains in a clear and simple way how to cultivate and manage cassava while preventing soil erosion on sloping land. The videos are prepared to deepen farmer’s understanding of the technical aspects of improved soil management, and at the same time, to prompt discussion within the local context.